The Effect of Digital Social Responsibility on Consumer Behaviour in the Mobile Telecom Industry (Marketing i Menedžment Innovacij)
This research aims to examine the relationship between perceived digital social responsibility (DSR) and consumer selection by mobile telecom companies in Saudi Arabia, considering purchase intention (PI) and consumer loyalty (CL), with the mediating role of brand preference (BP). This study found digital social responsibility to be a powerful marketing tool that can reach customers and increase sales volume, which is a significant addition for corporate social responsibility officers and marketing managers. Therefore, using social media platforms as a medium is important for influencing consumers’ attitudes toward and social responsibility for social media. Telecom companies need to focus on digital social responsibility strategies since there is high competition with similar services and products, making it difficult to earn consumer loyalty. The research strategy employed a positivist approach with a quantitative methodology, utilizing an online questionnaire. The data were collected from 375 Saudi participants and analysed using the Statistical Package for Social Sciences (SPSS) v.23 for hypothesis testing. The theoretical framework was tested using AMOS v.23 and structural equation modelling (SEM). Weak relationships were observed between perceived digital social responsibility and both PI and CL. However, a significant relationship existed between perceived DSR and BP. The most significant relationships were found between BP and both PI and CL. Thus, BP was identified as a partial mediator between perceived DSR and PI, as well as CL. This study highlights the importance of fostering long-term relationships between consumers and mobile telecom companies. Cultural differences may explain the contradictory findings of previous studies. There are several limitations in terms of the perception of digital social responsibility. In the Saudi context, participants seemed unfamiliar with the term. However, the use of a cross-sectional method prevented the research from measuring the change in participants' perceptions of digital social responsibility over time, making it difficult to measure purchase intentions and consumer loyalty. Additionally, no specific digital platforms, such as Facebook, Twitter, or Instagram, were used in this research, making it difficult to analyse each post and its impact. Moreover, future research should investigate small mobile telecom companies in Saudi Arabia.